2008
DOI: 10.1504/ijccm.2008.020008
|View full text |Cite
|
Sign up to set email alerts
|

Chinese brands: the build or buy considerations

Abstract: This paper discusses the strategic motives, the markets entered, the methods used and the challenges faced by Chinese companies building their own brand or buying one to expand globally. We present a regression model enabling the analysis of recent Mergers and Acquisitions (M&A) activities and the successes and failures between the Chinese and foreign target companies. The developed model considers the strategic motives to globalise, the type of country and acquisition. By using the Monte Carlo resampling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A recent phenomenon shows that Chinese firms are no longer focusing on domestic market and going 'global. ' Current researchers found that there are many underlying motives for Chinese firms to go global, in which 'creating a single and globally recognized brand' is one (Fetscherin and Sardy 2008;Fan 2006). Constantly, global firms remain focused on managing sales volume and brand equity by offering customers some values and beliefs which can stimulate purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…A recent phenomenon shows that Chinese firms are no longer focusing on domestic market and going 'global. ' Current researchers found that there are many underlying motives for Chinese firms to go global, in which 'creating a single and globally recognized brand' is one (Fetscherin and Sardy 2008;Fan 2006). Constantly, global firms remain focused on managing sales volume and brand equity by offering customers some values and beliefs which can stimulate purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…While these export figures are still relatively small by industry standards and there are still many challenges to overcome for manufacturers from both countries, it is probably a matter of time before they follow the example of Japan and South Korea and firmly establish themselves in foreign markets. In light of these developments, it seems appropriate to investigate how consumers in developed country markets will perceive cars that are manufactured in developing countries by developing country manufacturers and especially how their car brands are perceived (Fetscherin and Sardy 2008). The purpose of this paper is to investigate this increasingly important issue, focusing on the product category of automobiles from China and India.…”
mentioning
confidence: 99%